જો ${{{{({2^{n + 1}})}^m}({2^{2n}}){2^n}} \over {{{({2^{m + 1}})}^n}{2^{2m}}}} = 1,$ તો $m =$
$0$
$1$
$n$
$2n$
જો $x \ne 0 $ તો ${\left( {{{{x^l}} \over {{x^m}}}} \right)^{({l^2} + lm + {m^2})}}$${\left( {{{{x^m}} \over {{x^n}}}} \right)^{({m^2} + nm + {n^2})}}{\left( {{{{x^n}} \over {{x^l}}}} \right)^{({n^2} + nl + {l^2})}}=$
સમીકરણ ${4.9^{x - 1}} = 3\sqrt {({2^{2x + 1}})} $ નો ઉકેલ મેળવો.
જો ${2^x} = {4^y} = {8^z}$ અને $xyz = 288,$ તો ${1 \over {2x}} + {1 \over {4y}} + {1 \over {8z}} = $
$9\sqrt 3 + 11\sqrt 2 $ નું ઘનમૂળ મેળવો.
${{{{2.3}^{n + 1}} + {{7.3}^{n - 1}}} \over {{3^{n + 2}} - 2{{(1/3)}^{l - n}}}} = $